MODEL PEMBELAJARAN JEJARING SOSIAL PADA PELAJARAN MATEMATIKA - Fadli Fadli (Perspektif Ilmu Pendidikan, 2014)
The purpose of this research was to develop social-hub instructional model in teaching mathematics. Taking place in Government Madrasah Aliyah 3, Palembang as from January through June 2013, the research selected the science students of Grade XI as the respondents. As a research and development project, Borg and Gall model was combined with Dick and Carey model to develop social-hub instructional model. To test the model, this research applied experts, one-to-one, small group, and field tests focusing on the student’s interest and learning achievement. The fourth prototype proved the potential design to be effective in the instruction showing 65.63 % of the students interested in the model and the average of mastery learning was 82.66. The findings conclude, the model developed is valid and applicable in teaching mathematics and effective in improving the student’s learning motivation in mathematics.